LITERATURE REVIEW: EFFECT OF EXERCISE ON SERUM FGF23 - Nurunnisa Sholeha Letto; Vita Murniati Tarawan Lubis; Hanna Goenawan; Yuni Susanti Pratiwi; Titing Nurhayati (PAIFORI, 2021)
Exercise is an activity that has many health benefits, including bone, heart, and muscle health. One of the proteins found to be increased after exercise was FGF23. FGF23 is one of the bone mineral regulators which previously served as an indicator for chronic kidney disease severity and cardiovascular morbidity. However, some studies have found no increase in FGF23 after exercise. The purpose of this study is to elucidate the effect of exercise on serum FGF23. This study is a literature review with a qualitative approach comparing previous studies related to exercise and FGF23. From 13 selected kinds of literature, serum FGF23 elevation was found on exercise for one day to three weeks and did not change after six weeks to 12 months of exercise. The conclusions of the study are serum FGF23 was found to be increased after one day to three weeks of exercise and serum FGF23 in human studies found to be increased after long-duration maximal-intensity exercise.